Listeria monocytogenes membrane vesicles disrupting intestinal epithelial barrier function via modulating macrophage inflammatory responses - Yao Lei; Kehan Chen; Mingyuan Tang; Qiuyang Zhang; Jie Yu; Yunwen Zhang; Tian Tang; Chuan Wang (Interdisciplinary Medicine)
Abstract Bacterial extracellular vesicles (BEVs) are actively secreted nanostructures that play a unique role in the pathogenesis of bacterial infections. In this study, we established an intestinal epithelial cell (IEC)/macrophage coculture system and found that Listeria monocytogenes (LM) membrane vesicles (MVs) acted on macrophages and caused intestinal barrier disruption. Further studies revealed that LM MVs not only induced the M1‐type polarization in macrophages through the MAPK signaling pathway but also activated AIM2 and NLRP3 inflammasomes in macrophages to induce pyroptosis. The inflammatory factors IFN‐α and TNF‐α released by macrophages can bind to IFNAR and TNFR in IECs and activate the JAK‐STAT3 signaling pathway, disrupting the intestinal barrier. Our study illustrates the role and mechanism of LM MVs in disrupting the intestinal barrier by regulating the inflammatory response of macrophages, which helps understand the function of LM MVs, explains the mechanism of LM‐intestinal infection, and may provide new targets for the treatment of intestinal invasive infections with LM.